(untitled) (Acta Scientiarum. Biological Sciences, 2015)
The Brazilian prawn fishery, as other bottom trawling fisheries, is considered quite efficient in catching the target species but with low selectivity and high rates of bycatch. The family Sciaenidae prevails among fish species caught. The study was conducted in the Pernambuco State (Barra de Sirihaém), northeastern Brazil. From August 2011 to July 2012, 3,278 sciaenid specimens were caught, distributed into 16 species, 34.2% males and 41.5% females. Larimus breviceps, Isopisthus parvipinnis, Paralonchurus brasiliensis and Stellifer microps were the most abundant species. The area was considered a recruitment and reproduction area with the highest reproductive activity between December 2011 and July 2012. The constant frequency of mature I. parvipinnis and S. microps in catches throughout the year suggests that these species are multiple spawners and use the area during their reproductive period. Since most individuals caught as bycatch have not reached sexual maturity, evidencing the need for a better monitoring of the area and the Sciaenidae caught as bycatch, once this incidental caught can cause fluctuations in the recruitment, increasing the proportion of immature individuals in the population and negatively affecting the reproductive success of the species.